2015
DOI: 10.2749/101686615x14210663188574
|View full text |Cite
|
Sign up to set email alerts
|

Design Criteria of Under-Deck Cable-Stayed Composite Bridges for Short and Medium Spans

Abstract: Under-deck cable-stayed bridges are innovative bridge schemes that can lead to lightweight and highly efficient construction. However, the design of slender bridges may be governed by the vibrations under traffic live loads. After a historical review of bridges with under-deck cable-staying systems and the consequent research, the dynamic response of medium-and short-span bridges is analysed. Eccentric traffic loads are shown to increase accelerations considerably, and the second vertical mode is found to be t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 24 publications
3
5
0
Order By: Relevance
“…Three spans, namely 30 m, 60 m and 90 m, are chosen representing short-, medium-and long-span for TCC bridges, respectively. These spans are consistent with the most efficient span range identified in previous research [21,24]. It is shown that the post-tensioned under-deck tendons can significantly increase the slenderness of TCC bridges, and change the critical limit states governing their design.…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…Three spans, namely 30 m, 60 m and 90 m, are chosen representing short-, medium-and long-span for TCC bridges, respectively. These spans are consistent with the most efficient span range identified in previous research [21,24]. It is shown that the post-tensioned under-deck tendons can significantly increase the slenderness of TCC bridges, and change the critical limit states governing their design.…”
Section: Introductionsupporting
confidence: 89%
“…An attractive type of longitudinal post-tensioning, known as under-deck cable-stayed system, was introduced into bridge engineering in 1978 by Leonhardt in the Weitingen viaduct over the Neckar River in Germany [20]. In the last two decades, significant research has been conducted on the application of post-tensioned under-deck tendons to concrete and steel-concrete composite bridges [21,22,23,24,25]. However, little work has been done so far to promote the development of under-deck cable-stayed tendon systems in TCC bridges [19,26].…”
Section: Introductionmentioning
confidence: 99%
“…On one hand, p Mode 1 is the lowest critical load for lower K values, but for stiffness values K > 2, Mode 2 becomes the lowest critical load. This response has been also observed in the dynamic behaviour of UDCSBs [24,25], in which the second flexural mode is the natural mode when the axial stiffness of the cable-staying system is sufficiently high when compared with the bending stiffness of the deck.…”
Section: Critical Bucklingsupporting
confidence: 52%
“…It is also demonstrated that the schemes which have been proposed by the authors in previous work [24,25] as appropriate for medium spans (i.e. spans around 80 m) do not present any instability issues when considering realistic cross-section properties and prestressing loads.…”
Section: Discussionmentioning
confidence: 83%
“…The results of such calculations give an uneven tense state along the length of the main element -beams of rigidity, which consists of a significant difference in reference and flying moments. This makes the existing combined structures always rational [12][13][14]. Therefore, improving the method of calculating combined steel structures, which would reflect their actual work, is currently a actual problem.…”
Section: Introductionmentioning
confidence: 99%